2018
DOI: 10.3390/cryst8060232
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Characterizing Techniques in the Fine Structure Observation of Metal Halide Perovskite Crystal

Abstract: Driven by its appealing application in the energy harvesting industry, metal halide perovskite solar cells are attracting increasing attention from various fields, such as chemistry, materials, physics, and energy-related industries. While the energy conversion efficiency of the perovskite solar cell is being investigated often by various research groups, the relationship between the surface structure and the property is still ambiguous and, therefore, becomes an urgent topic due to its wide application in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 73 publications
(122 reference statements)
0
12
0
Order By: Relevance
“…The most widespread techniques used for in situ and operando studies of the perovskite crystal structure are standard X-ray diffraction (XRD) and grazing incidence X-ray scattering in small angle or wide angle configuration (GISAXS/ GIWAXS, respectively). [9][10][11] In contrast to the transmission configuration, grazing incidence allows for experimental designs that require a non-X-ray transparent sample stage such as a hotplate in annealing studies.…”
Section: In Situ/operando X-ray Scattering Methodsmentioning
confidence: 99%
“…The most widespread techniques used for in situ and operando studies of the perovskite crystal structure are standard X-ray diffraction (XRD) and grazing incidence X-ray scattering in small angle or wide angle configuration (GISAXS/ GIWAXS, respectively). [9][10][11] In contrast to the transmission configuration, grazing incidence allows for experimental designs that require a non-X-ray transparent sample stage such as a hotplate in annealing studies.…”
Section: In Situ/operando X-ray Scattering Methodsmentioning
confidence: 99%
“…It can be used to grow single crystals for some perovskite materials in particular solvents, in which different solubility can be observed in different temperatures. [52] For example, the solubility of some perovskite materials in an HX-based solvent will decrease with a lower solution temperature. (Figure 1a) [42] In 1987, Weber et al used STL method to grow single crystals of CH 3 NH 3 PbX 3 (X = Cl, Br, I) by cooling a concentrated aqueous solution of HX acid, Pb 2 + and CH 3 NH 3 + from about 100°C to room temperature.…”
Section: Solution Temperature Lowering (Stl) Methodsmentioning
confidence: 99%
“…This principle of this method is to obtain single crystals by slowly lowering the temperature, which can reduce the solubility of the solute and make a single crystal precipitate while the solute is saturated in solution. It can be used to grow single crystals for some perovskite materials in particular solvents, in which different solubility can be observed in different temperatures . For example, the solubility of some perovskite materials in an HX‐based solvent will decrease with a lower solution temperature.…”
Section: Single Crystal Growth Of Organic‐inorganic Perovskitesmentioning
confidence: 99%
“…Understanding their phase stability and local structure or characterizing the material in situ as a photovoltaic device are the types of studies that have been reported. [119][120][121][122][123][124][125][126][127] Amorphous nanoparticles are of interest due to their applications in catalysis, optics, magnetism, bioactivity, electrochemistry, and nanocomposites. [128][129][130][131][132][133][134] In particular, there are cases within the water oxidation catalysis literature where the amorphous materials have produced superior catalytic activity to their crystalline counterparts.…”
Section: Additional Systems Of Interest: Perovskites Quaternary Nanocrystals Amorphous Nanoparticles and Carbon Dotsmentioning
confidence: 99%